The Effect of Different Storage Temperatures and Internal Analysis of Onions with X-Ray CT on The Respiration Rate of Onions - Rahmah An Nidaa’ Fatkhur; Priyanti Devi; Ayuningsih Ira; Nugraha Bayu (E3S Web of Conferences, 2023)
Onion is an agricultural product that will continue to respirate after harvesting. Internal factors affecting the respiration rate are shelf life, onion type, and water levels external factors derived from the affected environment are temperature and RH. This study aimed to determine the difference in the rate of onion respiration with different storage temperatures. The samples used are local onion batu ijo. The onions for each sample are weighed 300 grams, then put in a sealed respiratory jar and stored at 27 ± 2oC and 7 ± 2oC temperature. The change in O2 and CO2 levels is measured using an analytical gas at a time interval of 1 hour in the first 12 hours, then every 8 hours in the following 60 hours, every 12 to 144 hours, and every 24 to 432 hours. The O2 consumption and CO2 production respiration rate equations perform the analysis. The results showed that temperature affected the onion respiration rate. Then, a non-destructive analysis of the internal damage of onions during storage in modified air conditions using X-Ray CT is also carried out. This analysis was performed to determine whether non-destructive analysis using X-Ray CT could be applied to see the damage to onions internally.